Leveraging nitrogen occurrence in approved drugs to identify structural patterns - Masand, Vijay H; Al-Hussain, Sami; Alzahrani, Abdullah Y.; El-Sayed, Nahed N.; Yeo, Chien Ing *; Tan, Yee Seng *; Zaki, Magdi E A (Taylor and Francis Group, 2024)
Background The process of drug development and discovery is costly and slow. Although an understanding of molecular design principles and biochemical processes has progressed, it is essential to minimize synthesis-testing cycles. An effective approach is to analyze key heteroatoms, including oxygen and nitrogen. Herein, we present an analysis focusing on the utilization of nitrogen atoms in approved drugs.